The Mission of the American Board in Syria Implications of a transcultural dialogue - Zeuge-Buberl, Uta (Franz Steiner Verlag, 2017)
The work of Christian missions in past centuries has persistently been viewed in a negative light, although missionaries did not always act with cultural imperialist or colonialist intent. This volume presents a more nuanced interpretation of mission work, illuminating the significance of interpersonal interactions within the mission field. The Syria Mission of the American Board of Commissioners for Foreign Missions (ABCFM), which was active in the Ottoman Province of Syria (present-day Lebanon) between 1819 and 1870, provides the study's central focus. The study analyzes cultural exchange between the Ottoman Empire and the United States through the example of four important protagonists whose significance has been neglected in previous historical scholarship on missions: the missionaries Eli Smith and Cornelius Van Dyck, as well as the Syrian Protestants Butrus al-Bustani and John Wortabet.